2017
DOI: 10.1039/c7pp00112f
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenylbenzoxazole derivatives: a family of robust emitters of solid-state fluorescence

Abstract: The derivatives of 2-phenylbenzoxazole (PBO) are popular fluorescent organic dyes for use in solution or after dispersion in an appropriate matrix. Their spectroscopic behavior in the solid state is, unjustly, not so well known. Many of them are strongly emissive as pure solid dyes, due to a favorable crystal packing mode. The PBO fragment lends itself well to relatively simple modifications of its chemical structure, aimed at enlarging the conjugated π-electron system. Many molecules thus designed show aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 116 publications
2
31
0
Order By: Relevance
“…This work confirms our assumption that extending the electron conjugation of the PBO framework with a CH=CR 1 R 2 group inserted on the phenyl ring is enough to get AIEE behaviour, which is accompanied here by a MFC effect. The small dicyanovinyl group can be easily introduced in a large variety of dye molecules, and it would be instructive to know to what extent it can endow them with effective AIE/AIEE and MFC properties.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This work confirms our assumption that extending the electron conjugation of the PBO framework with a CH=CR 1 R 2 group inserted on the phenyl ring is enough to get AIEE behaviour, which is accompanied here by a MFC effect. The small dicyanovinyl group can be easily introduced in a large variety of dye molecules, and it would be instructive to know to what extent it can endow them with effective AIE/AIEE and MFC properties.…”
Section: Discussionsupporting
confidence: 89%
“…Alternatively, it has recently been shown that the electrostatic field induced on a single molecule by the crystalline environment is enough to rationalize AIE/AIEE effect . It is noteworthy that the strong red shift of the emission spectrum observed upon aggregation compares well with that reported for benzoxazole styryl dyes, the π‐electron conjugated system of which is larger than that of compound 1 …”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, all halogen substituted molecules showed halogen interaction in the solid state with opposite molecular arrangement. Rigidification and restriction of intramolecular rotation (RIR) of fluorophores in the solid state via supramolecular interactions plays important role for enhancement of fluorescence by deactivating the non‐radiative process . Comparison of solid‐state structure and fluorescence efficiency suggest that dimer with opposite molecular orientation in para ‐F and meta and para ‐Br showed enhanced fluorescence than 1, meta ‐F and meta ‐Cl.…”
Section: Resultsmentioning
confidence: 99%
“…It includes photoexcitation of am olecule in the enol form, S 0 e !S 1 e ,afast enol-to-keto S 1 e !S 1 k ESIPT (k ESIPT % 10 12 s À1 )a nd, finally,t he S 1 k !S 0 k emission in the keto form followedb yf ast ground state intramolecular protont ransfer (GSIPT), S 0 k !S 0 e . [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The ESIPT leads to significant spatials eparation of HOMO and LUMO which reduces the singlet-triplet (S 1 -T 1 )e nergy separation, DE ST . [17] Importantly,s mall DE ST values ( 0.2 eV or 19 kJ mol À1 )f acilitatet hermally activated delayedf luorescence (TADF).…”
mentioning
confidence: 99%